Pengembangan Pemasaran Dental Tourism Sebagai Peluang Bisnis Kesehatan Pariwisata di Bali - Sagung Agung Putri Dwiastuti; Ida Ayu Dewi Kumala Ratih; Jusuf Kristianto (Jurnal Health Sains, 2023)
The Minister of Tourism and Creative Economy (Menparekraf) Sandiaga Uno launched Bali as a health-based tourism destination (medical tourism), this was done to create jobs and restore the glory of the Island of the Gods tourism sector. Dental Tourism is a business opportunity to invite tourists besides enjoying the beauty of nature, dental care packages are included, moreover there are lots of non-emergency dental treatments. Phase 1 research aims to find out what is the motivation, and the level of satisfaction with dental tourism services in Bali in 2022. The method used is the Delphi method, and quantitative data collection is carried out using a questionnaire. Descriptive statistical analysis tests are calculated using SPSS Version 20. Reliability of the dimensions of motivation and satisfaction is analyzed using Cronbach's Alpha. The reliability of the motivation and satisfaction dimensions were analyzed using Cronbach's Alpha. The results obtained from 342 respondents, 51.8% more women than men, with the origin of the respondents from abroad, the most from Australia (60.5%), and related to dental care as many as (21.7%) willing to do dental work. filling and as many as (17%) want to do scaling when doing dental treatment in Bali. In terms of motivation, most (75.7%) of respondents have good driving motivation and most (76.9%) have good pull motivation to do dental treatment in Bali. The chi-square test showed that push motivation and pull motivation had a relationship with the satisfaction received by respondents after doing dental treatment in Bali (p <0.05). Where if someone has a better push and pull motivation, then there is a greater chance of getting satisfaction after doing dental treatment in Bali. The results of multivariate analysis show that a good driving motivation has a 1.5 times greater chance of obtaining satisfaction after doing dental treatment in Bali. Meanwhile, someone who has a good pulling motivation has a 2.8 times greater chance of getting satisfaction after doing dental treatment in Bali.